Combined Hamartoma of Retina and Retinal Pigment Epithelium: Multimodal Imaging and Management - Mohd Azaz Quraishi; Kaustubh Revatkar; Amit S. Nene; Smitesh Shah; Pratik Shenoy; Pushpanjali Ramteke; Onkar H. Pirdankar (Delhi Journal of Ophthalmology)
Combined hamartoma of the retina and retinal pigment epithelium (CHRRPE) is a rare condition which typically comprises of slightly elevated grayish mass located at the posterior pole. It is commonly associated with proliferative membrane leading to distorted vasculature. Severe cases may present with a macular hole, retinal detachment, or vitreous hemorrhage. Here, we detail the management of a CHRRPE case in a 74-year-old female who underwent pars plana vitrectomy with epiretinal membrane peeling, resulting in improved anatomical and visual outcomes.